Fighting disease and epidemics: Ricardo Jorge and the internationalization of Portuguese science - Almeida, M. A. P. de (Vesalius: Acta Internationalia Historiae Medicinae, 2013)
Ricardo Jorge was one of the principal doctors responsible for the sanitary transition in Portugal. He created and enforced the most important policies for disease control, both endemic and epidemic, which scourged the western world between the mid nineteenth century and beginning of the twentieth. His professional training and academic and scientific performances reveal Ricardo Jorge's value in Portuguese science and his efforts for its internationalization. His capacities were confirmed by the emergency of the sanitary situations with which he was confronted and by the authorities' confidence in him, by putting him in charge of the bubonic plague elimination process.